2016
DOI: 10.1097/ncc.0000000000000341
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Taiwanese Version of the General Fatigue Scale in Cancer Patients

Abstract: The GFS-T can provide clinical nurses with a useful measure to assess fatigue in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For the first section, scores of 0, 1–4, 5–6, and 7–10 indicate no, mild, moderate, and severe fatigue, respectively. For the second section, higher scores indicate greater interference; specifically, scores of 0, 1–4, 5–6, and 7–10 indicate no, mild, moderate, and severe fatigue, respectively, and a corresponding severity of interference [ 40 ]. In the present study, the Cronbach’s alpha values for the Chinese version of the BFI-T were 0.90, and 0.92 for fatigue severity and fatigue inference, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…For the first section, scores of 0, 1–4, 5–6, and 7–10 indicate no, mild, moderate, and severe fatigue, respectively. For the second section, higher scores indicate greater interference; specifically, scores of 0, 1–4, 5–6, and 7–10 indicate no, mild, moderate, and severe fatigue, respectively, and a corresponding severity of interference [ 40 ]. In the present study, the Cronbach’s alpha values for the Chinese version of the BFI-T were 0.90, and 0.92 for fatigue severity and fatigue inference, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The General Fatigue Scale (GFS) is a 7-item scale that assesses overall fatigue intensity, distress level and disruptions of daily activity, and was designed to use for randomized controlled trials to measure fatigue at specific timepoints [98]. The scale was validated and translated into Chinese [98]; the Cronbach's alpha reliability coefficient was 0.94. In people with cancer, the GFS met the quality assessment criteria for content validity, construct validity, internal consistency and reliability.…”
Section: Section Two: Scale Characteristicsmentioning
confidence: 99%
“…Fatigue was measured using the GFS‐T (Chou et al, 2016). It is comprised of 7 items that assessed the level of fatigue today, most days, at its highest in the past 48 h and past week and the general intensity, distress and impact of fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…A factor analysis showed that one factor explained 73.7% of the variance in fatigue. A cut‐off score of 24 had an adequate combination of sensitivity (82%) and specificity (52%) to distinguish high and low performance status, with an area under the receiver operating characteristic (ROC) curve of 0.67 (95% confidence interval [CI]: 0.59–0.75) (Chou et al, 2016). The Cronbach's α of the GFS‐T was .95 in this study.…”
Section: Methodsmentioning
confidence: 99%